WADAH AKTIVITAS TEMPORER DI RAWA BUAYA - Adelia Putri Octavini; Dewi Ratnaningrum (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
The lives of many Jakarta people are spent in the residence (first place) and the workplace (second place). Lack of community interaction outside these two places makes people feel unfamiliar with the surrounding environment to cause prejudice and even crime (Theory of Deindividuation). Humans tend to feel more secure about the surrounding environment if they can get to know the people around him. The density of Jakarta is accompanied by a variety of activities that have not been properly enclosed. Spatial optimization using the planning of space temporality is manifested in the portability of architecture and program planning. To bring the community together, a temporary activity place (Tempo. Act. Place) is designed in Rawa Buaya. This site was chosen because it has a high diversity of the community. The method used is quantitative and qualitative methods, which is a grounded observation, interviews, and a literature review. The program in this building is realized through some zones, which are the Temporary Event Zone, the Knowledge Sharing Zone, the Pocket Farming Zone, and the Commercial Zone. The zone is planned to bring togetherness and trigger the needs of users so they can interact with each other. Organizing space is also formed through the approach of Social Psychology theory, namely Functional Distance. The shape of the building was inspired by the metamorphosis of the Liquid Phase theory in Temporary City which was realized in the form of cones. Then the curved floor plan following the cone made the building more dynamic. So that the third-place character that are playful mood, a conversation is the main activity, and neutral can be fulfilled. AbstrakKehidupan masyarakat Jakarta banyak dihabiskan di tempat tinggal (first place) dan tempat bekerja (second place). Kurangnya interaksi masyarakat di luar dua tempat tersebut membuat masyarakat merasa asing dengan lingkungan sekitarnya hingga menimbulkan prasangka dan kejahatan (Theory of Deindividuation). Manusia cenderung merasa lebih aman terhadap lingkungan sekitarnya, apabila ia dapat mengenal orang sekitarnya. Kepadatan kota Jakarta diiringi beragam aktivitas yang belum terwadahi dengan baik. Pengoptimalan ruang menggunakan sifat kesementaraan ruang terwujud dalam portabilitas arsitektur dan perencanaan program yang berfungsi mewaktukan ruang. Untuk mempertemukan masyarakat, direncanakan sebuah wadah aktivitas yang bersifat temporer yang berada di Rawa Buaya. Lingkungan ini dipilih karena memiliki keberagaman yang tinggi. Metode yang dipakai adalah metode kuantitatif dan kualitatif, yaitu berupa observasi grounded, wawancara, dan kajian literatur. Program ruang dalam bangunan ini terwujud melalui zona yang ada, yaitu Zona Temporary Event, Zona Knowledge Sharing, Zona Pocket Farming, dan Zona Komersil. Zona tersebut direncanakan untuk mempertemukan dan memicu kebutuhan antar pengguna sehingga dapat saling berinteraksi. Pengorganisasian ruang juga dibentuk melalui pendekatan teori Psikologi Sosial, yaitu Functional Distance. Bentuk bangunan terinspirasi dari metamorfosa teori Liquid Phase di Temporary City yang diwujudkan dalam bentuk cone. Kemudian bentuk denah yang melengkung mengikuti cone tadi membuat bangunan menjadi lebih dinamis. Sehingga karakter third place dapat terpenuhi, yaitu playful mood, conversation is the main activity, dan neutral.